Obstructive Sleep Apnea dan Gagal Jantung - Purwowiyoto, Sidhi Laksono (Lembaga Penelitian Universitas YARSI, 2017)
Obstructive sleep apnea (OSA) is a part of sleep-disordered breathing which is commonly found in the population of heart failure. Epidemiological studies have shown significant independent associations between OSA and heart failure. OSA plays an important role in the pathogenesis and progression of heart failure. Several pathogenesis are the mechanical effect, activation of sympathetic, inflammation process, and endothelial dysfunction. These can impair myocardial contractility and cause development and progression of heart failure. However, the prevalence OSA is only the “tip of the iceberg” due to the difficulty in diagnosis. Most of OSA patients, particularly in the heart failure population, have no complaint of the sleepiness.